Taxonomic review of the family Throscidae Laporte, 1840 (Coleoptera: Elateroidea) in Korea, the description of a new species with new generic and species records - Seung, Jinbae; Han, Taeman; Lee, Seunghyun; Lee, Minhyeuk; Lee, Seunghwan (Zootaxa, 2024)
The family Throscidae (Coleoptera: Elateroidea) is taxonomically reviewed from Korea. To date, the taxonomic study on Throscidae from Korea is insufficient, as only a single species has been reported in the fauna prior to this study. We newly recognized three species belonging to the genus Aulonothroscus, which is recorded for the first time from Korea. A new species, Aulonothroscus koreanus sp. nov., is described and two additional species are reported as new to Korea: Aulonothroscus laticollis (Rybiński, 1897) and Aulonothroscus longulus (Weise, 1879), raising the total number of known species of Korea to four. Herein, we provide a key to genera and species, descriptions, and images of diagnostic morphological features of the Throscidae fauna of Korea.